Chromobacterium Violaceum: A Model for Evaluating the Anti-Quorum Sensing Activities of Plant Substances - Petya D. Dimitrova; Tsvetozara Damyanova; Tsvetelina Paunova-Krasteva (MDPI AG, 2023)
In the new antibiotic era, the exponential increase in multiresistant bacterial strains has become the main global health problem. Many researchers have focused their efforts on exploring novel or combined strategies for combating bacterial resistance. Good knowledge of the molecular mechanisms of resistance and bacterial virulence factors as key targets provides us with a good basis for resolving the problem. One particularly attractive and promising strategy is to attack the main regulatory "network" of bacterial virulence determinants known as quorum sensing (QS). The inhibition of QS signals will be a novel means of screening more effective quorum-sensing inhibitors (QSIs) and will play a key role in the use of next-generation antimicrobials in the battle against resistance. This motivated the present review to provide a comprehensive clarification of the regulatory mechanisms of quorum-sensing signaling pathways in Chromobacterium violaceum and the discovery of potential plant quorum-sensing inhibitors.